Regional beta‐amyloid and tau deposition: Results from the Framingham Heart Study. (5th January 2022) - Thibault, Emma G.; Farrell, Michelle E.; Beiser, Alexa S.; Sanchez, Justin S.; Satizabal, Claudia L.; Mayblyum, Danielle V.; O'Donnell, Adrienne; Rubinstein, Zoe B.; Jacobs, Heidi I.L.; DeCarli, Charles S.; Hanseeuw, Bernard; Killiany, Ronald J.; et al.
Abstract: Background: The Framingham Heart Study (FHS), a three‐generation community‐based cohort studying cardiovascular disease across the adult lifespan, has expanded to include positron emission tomography (PET) of beta‐amyloid (Aβ) and tau. Our aim is to characterize these pathologies in this unique sample and utilize the wide age range to assess the spatiotemporal ordering of emerging Aβ and tau. Method: 211 clinically‐normal adults aged 33‐74 from FHS underwent Pittsburgh Compound B (PIB) and Flortaucipir (FTP) PET. PIB and FTP were regionally quantified in Desikan regions using distribution volume ratio (DVR) for PIB and standardized uptake volume ratio (SUVR) for FTP. Three approaches were used to identify early accumulating regions: 1. A series of Age*APOE linear models to identify regions accumulating earlier in the lifespan in ε4 carriers. 2. Identification of early regions as those more frequently elevated as previously used in older adults, with Gaussian mixture models (GMM) conducted to evaluate bimodality and set biomarker positivity thresholds for each region. 3. Applied the same frequency approach using well‐validated PIB GMM thresholds based on older adults from the Harvard Aging Brain Study (HABS). Result: For PIB, significant Age*APOE interactions (Fig. 1) were seen across multiple regions previously implicated as early‐accumulating based on elevation frequencies from older adult samples, as well as the pars opercularis (p=0.005) and lateral parietal cortices (p<0.04). PIB was significantly bimodal across all ROIs (LRT>36.1, p<0.001; Fig. 1). Application of GMM‐based regional positivity frequencies derived within FHS versus from HABS thresholds led to substantial discrepancies in the spatiotemporal ordering of PIB ( r s =0.30, p=0.17). Age*APOE effects were not detected for any tau regions, but inferior temporal (IT), middle temporal (MT), and amygdala (AM) increased with age (Fig. 2). Higher global Aβ was also associated with higher FTP SUVR in IT, MT, and a trend for AM, as well as inferior parietal and precuneus (Fig. 2). Conclusion: Aβ and tau mainly follow spatiotemporal patterns consistent with prior evidence in older adult samples. GMM‐based methods used in older adult samples to dichotomize biomarker positivity may be suboptimal in younger samples. Continuous approaches may better capture early Aβ and tau in younger populations.